The Private Healthcare Insurance sector: A victim of fraud. Issue 1 (March 2022) - Brooks, Graham; Stiernstedt, Peter
Regardless of the jurisdiction research has repeatedly highlighted that the 'public' see the insurance sector as an acceptable business to defraud. This article builds on this work but is different in that we draw on primary research, of which there is little, into the private healthcare insurance sector as a victim of fraud. We start by highlighting the types and volumes of fraud that the insurance sector encounters. This is followed with an examination of policing private insurance fraud in a neo-liberal context where individuals and organisations are responsible for risks. Then, we consider if the private healthcare insurance sector is precipitating and participating in its own victimisation. The methods used in this research to secure data are then explained. Finally we analyse how the key elements of the data might point to the private healthcare insurance sector potentially precipitating and participating in its own victimisation.